Multi-criteria approach for weights definition of sustainability indicators in the swine supply chain - Silvana Kruger; Flavio Trojan; Antonio Zanin; Mauro Lizot; Paulo Afonso (Brazilian Journal of Operations & Production Management)
Goal: This study presents a four-steps methodology for the definition of the weights of sustainable indicators in the Swine Supply Chain (SSC) considering the Triple Bottom-Line (TBL) perspective.